ASESMEN PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA 5–6 TAHUN MELALUI KEGIATAN BERMAIN BALOK DI TK NEGERI PEMBINA LUBUK PAKAM - Wiwin Kristiani Waruwu; Anita Yus (STKIP Subang, 2026)
This study aims to describe the assessment of social-emotional development of children aged 5–6 years through block play activities in TK Negeri Pembina Lubuk Pakam. This research employs a descriptive qualitative method with a field study approach. Data were collected through interviews with teachers and documentation analysis, including lesson plans (RPPH), learning achievement indicators (IKTP), and children's development records. The results show that social-emotional indicators stimulated in block play include cooperation, communication, sharing, and emotional control, although not all indicators are formulated specifically. The assessment process is conducted naturally through direct observation during play activities but has not been systematically planned and documented. Furthermore, children’s social-emotional development varies, with some children demonstrating good abilities, while others still require guidance. The findings indicate that although assessment practices have been implemented, improvements are needed in terms of structured planning, clear indicators, and systematic recording to optimize learning outcomes.